Epidemiologic factors associated with endometriosis in East Asia - Chih-Feng Yen; Mee-Ran Kim; Chyi-Long Lee (Wolters Kluwer Medknow Publications, 2019)
Aim: With a perplexing pathogenesis and an incidence rate of approximately 10% among women of reproductive age, endometriosis affects more women in Asia than in any other continent in the world. This paper reviews the available data on the epidemiology and risk factors associated with endometriosis in East Asia. Methods: Included studies were published between January 2000 and December 2016. Articles were required to include East Asian patients with a diagnosis of endometriosis and to study epidemiology, such as the prevalence and/or incidence, associated with inherited, environmental, and/or lifestyle factors. A total of 65 candidate articles were retrieved and 22 were included in the final review. Results: Only one study provided an estimate of prevalence (6.8%). Short menstrual cycle, family history of endometriosis, and some genetic polymorphisms are associated with the risk of developing endometriosis. Smoking, lower body mass index, and lower parity associated with increased risk of endometriosis were suggested as modifiable factors. Limitations of this study include the poor quality of data identified, and the language barriers behind the study retrieval. Conclusions: Data on the epidemiology of endometriosis in the East Asian populations are limited. The available data that examine potential genetic factors do not unveil whether such factors directly contribute to the increased risk of endometriosis. Further extensive studies on endometriosis in Asian women are required to improve the management of this disease.